2023
DOI: 10.1002/acr.25169
|View full text |Cite
|
Sign up to set email alerts
|

Global Perspective on the Impact of the COVID‐19 Pandemic on Rheumatology and Health Equity

Abstract: Although the public health emergency associated with the COVID‐19 pandemic has ended, challenges remain, especially for individuals with rheumatic diseases. We aimed to assess the historical and ongoing effects of COVID‐19 on individuals with rheumatic diseases and rheumatology practices globally, with specific attention to vulnerable communities and lessons learned. We reviewed literature from several countries and regions, including Africa, Australia and New Zealand, China, Europe, Latin America, and the US.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…25 And a review summarising literature from Africa, Australia and New Zealand, China, Europe, Latin America and the USA showed that individuals with rheumatic diseases during the pandemic faced disruptions in healthcare and medication supply shortages. 26 However, many of these studies rely on small local samples or people with certain diseases and do not explore whether the decline in service utilisation is a result of reduced or unmet demand. Additionally, most studies only observe changes in outcomes before and after the pandemic, without differentiating whether these changes are specifically attributed to the effects of the pandemic or reflect general temporal trends over the same period due to other factors.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…25 And a review summarising literature from Africa, Australia and New Zealand, China, Europe, Latin America and the USA showed that individuals with rheumatic diseases during the pandemic faced disruptions in healthcare and medication supply shortages. 26 However, many of these studies rely on small local samples or people with certain diseases and do not explore whether the decline in service utilisation is a result of reduced or unmet demand. Additionally, most studies only observe changes in outcomes before and after the pandemic, without differentiating whether these changes are specifically attributed to the effects of the pandemic or reflect general temporal trends over the same period due to other factors.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%